Adherence to a healthy sleep pattern is associated with lower risks of incident falls and fractures during aging - Zhou, Tao; Dai, Xue; Yuan, Yu; Xue, Qiaochu; Li, Xiang; Wang, Mengying; Ma, Hao; Heianza, Yoriko; Qi, Lu (Frontiers in Immunology, 2023)
We used a newly developed sleep pattern including early chronotype, sleep 7-8 h per day, no frequent insomnia, no snoring, and no frequent excessive daytime sleepiness as healthy factors to study their relationship with the incidence of falls and fractures. The analysis was conducted among 289,000 participants from the UK Biobank.During an average follow-up of 12.3 years (3.5 million person-years), we documented 12,967 cases of falls and 16,121 cases for all fractures. Compared with participants with an unfavorable sleep pattern (healthy sleep score 0-1), those with a healthy sleep pattern (healthy sleep score 4-5) had 17% and 28% reduced risks to have incident falls (HR, 0.83; 95% CI, 0.74-0.93) and all fractures (HR, 0.72; 95% CI, 0.66-0.79) during follow up. In addition, we found that participants with a healthy sleep pattern and a high genetically determined bone mineral density (BMD) showed the lowest risks of falls and fractures.A healthy sleep pattern was significantly associated with lower risks of incident falls and fractures. The protective association was not modified by genetically determined BMD.